Intercultural Communication In The Inheritance Urang Pulo The Myth - Euis Hermawati (KOM & REALITAS SOSIAL, 2011)
Communication is an essential aspect fo Urang Pulo to preserve their mythical culture. One of the myth preserving method is to inherit in the myth to upcoming generation. The inheritance involves both interaction and communication among Urang Pulo s society. Who share similar cultural backgrounds, which called intracultural communication. This study defines intracultural communication within Urang Pulo society. In the myth preserving method. The society of Kampung Pulo is unique, they are Sundanese sub-culture with matrilineal system where the ones who privilege to stay in this traditional village is the daughter of motherhood family, tree who happen to be the descendant ofAmbah Arif Muhammad. Kampung Pulo s society is bind to myth, thet has been inherited through generations.This study is a qualitative research using etnography communication approach, data collecting method is introspection, policipani observation, deep interview and document analytical.The result show that 1) intracultural communication in the main family at Kampung Pulos society has an important role in the myth to the next generation. The role of parents is done by implanting, and teach whatever myths prevailing in Kampung Pulo, by telling stories and perform traditional rituals. Mother or grandmother is the main is the main source of information for the whole family, they were not separated by historical, that the people of Kampung Pulo known for matrilinealnya system. These myths are the legacy of Kampung Pulo ancestor society that must be maintained and preserved. 2) The symbols that are being used are divide into two, Symbols tangible thas is house tradition, offerings, nyuguh, padaringan, and symbols intangible that is, myth (pamali), kuruhun, and mamala. These symbols are not picked by the informants, instead has already been provided throughout generations based on cultural tradition. Languange is a symbol of the most frequently on myth preserving method. 3) Currently Urang Pulo, conceptualizing the inheritance of myth. Diversity in various ways of meaning is influenced by many things, such as education, experience, environment, age, generation, interaction with outsiders. Researcher categorized the meanings the were told by informants as process in myth preserving method to other generations; a) Gratefulnes to God. b) An honor to the ancestors. c) Fear of punishment. d) Direction of life to their descendants, and, e)Local wisdom. 4) Intacultural communication model of Urang Pulo is vertical, where the mechanism of communication is done from top to bottom, from one generation to next generation, intraculture communication Urang Pulo is done in the process of inheritance of myth, everyting is done face communication.